Two new species of chewing lice in the genus Melinirmus (Phthiraptera, Ischnocera, Philopteridae) from Australian honeyeaters (Passeriformes, Meliphagidae) - Daniel R. Gustafsson; Sarah E. Bush (Travaux du Muséum National d’Histoire Naturelle “Grigore Antipa”)
Two new species of the genus Melinirmus Mey, 2017, are described from Australian honeyeaters (Meliphagidae). These are: Melinirmus coromandelica n. sp. ex Ptilotula penicillatus penicillatus (Gould, 1837) and Melinirmus palmai n. sp. ex Anthochaera carunculata (Shaw, 1790). A checklist of all known species of Brueelia-complex chewing lice known from the Meliphagidae is provided.